IDENTIFIKASI SENYAWA BIOAKTIF ANTIFEEDANT DARI ASAP CAIR HASIL PIROLISIS SAMPAH ORGANIK PERKOTAAN - Haji, Abdul Gani; Mas’ud, Zainal Alim; Pari, Gustan (Bumi Lestari; Vol 12 No 1 (2012), 2012)
The research aims to identify antifeedant bioactive substance in liquid smoke derived from pyrolisis of organic municipal waste. Samples were pyrolyzed in drum reactor at 505oC for five hours to produce char and condensed smoke turning into liquid smoke. The liquid smoke components are separated into n-heksan, etil asetat, metanol and water consecutively. The result is thickened with rotary evaporator. The resulting crude’s activity towards Spodoptera litura Linn larvae was tested with antifeedant method. The chemical components of active fraction are identified with GCMS. Crude resulting from thickening fractions of n-heksan, etil asetat, metanol and water are 0.3465 g; 2.3736 g; 0.8775 g and 0.3679 g consecutively. The highest activity of liquid smoke, fractions of water, methanol, etil asetat and n-heksan towards S. litura larvae at 1.00% concentration are 44.68%; 62.07%; 80.65%; 28.57% and 23.40%. Result of probit analysis towards these fractions shows that the highest activity is methanol fraction with EI50 value at 0.71. Identification with GCMS shows that the fractions contain 14 types of bioactive antifeedant substances with ?-butyrolacton as the main component
Keywords: bioactive antifeedant, liquid smoke, pyrolisis, organic municipal waste